Detailed Multiband Electromagnetic Wave Absorption Study on Nanocrystalline (1-x)NiFe2O4/(x)BaTiO3 Composites - E. Sukirman; Y. Sarwanto; S. Ahda; Y. Taryana; S. Purwanto (Newest Updates in Physical Science Research Vol. 2, 2021)
Multiband electromagnetic wave absorption have been studied on nanocrystalline (1-x)NiFe2O4/ (x)BaTiO3 composites. The samples were synthesized by solid state reaction from the powder raw materials of BaTiO3 (BTO) and NiFe2O4 (NFO) compounds using high energy milling (HEM) instrument. Then the BTO and NFO were calcined and manually mixed with a weight percent ratio of NFO:BTO was 0:100, 34:66, 50:50, 60:40, and 100:0, hereinafter referred to K-1, K-2, K-3, K-4 and K-5, respectively. Then the five samples were pressed into pellets and then sintered. Then the five composite samples were characterized to determine whether or not the phase of the synthesized materials have been formed as expected. Therefore, a qualitative analysis with X-ray diffraction technique using X-ray Diffractometer (XRD) was performed. X-ray diffraction data was analyzed with the help of GSAS software. The magnetic properties of the material were observed with the aid of the vibrating sample magnetometer (VSM) instrument. The X-ray diffraction (XRD) patterns of all the samples show single phase and free from impurities. The sample K1 can be indexed to a single cubic crystal structure of NFO with a space group of Fd-3m, No. 227. While, the sample K5 can be indexed to a single tetragonal crystal structure of BTO with a space group of P4mm, No. 99. While K2, K3, and K4 is a composite consisting of two phases, namely NFO and BTO. All the samples show soft magnetic performance. The mass magnetization is in the range of 20.0–49.0 emu/g. The electromagnetic parameters of the composites were measured by a vector network analyser in the frequency range of 2 GHz to 18 GHz. The results indicated that (1-x) NiFe2O4 / (x) BaTiO3 composites display three-band electromagnetic wave absorption. The 0.5NiFe2O4 / 0.5BaTiO3 composite displays three-band reflection loss which is larger than the other one and the three-band reflection loss are almost the same, i.e., below the -15 dB. From these experiments it can be concluded that the 0.5NiFe2O4 / 0.5BaTiO3 composite is good candidate for electro-magnetic wave absorption.